Understanding without Justification and Belief? - Seungbae Park (Principia: An International Journal of Epistemology)
Dellsén (2016a) argues that understanding requires neither justification nor belief. I object that ridding understanding of justification and belief comes with the following costs. (i) No claim about the world can be inferred from what we understand. (ii) We run into either Moore’s paradox or certain disconcerting questions. (iii) Understanding does not represent the world. (iv) Understanding cannot take the central place in epistemology. (v) Understanding cannot be invoked to give an account of scientific progress. (vi) It is not clear how misunderstanding arises.